2018
DOI: 10.1190/geo2017-0123.1
|View full text |Cite
|
Sign up to set email alerts
|

Variations of attenuation and VP/VS ratio in the vicinity of wastewater injection: A case study of Costa Molina 2 well (High Agri Valley, Italy)

Abstract: By analyzing seismicity induced by the injection of wastewater into the Costa Molina 2 well, we characterized attenuation in the area. Attenuation quality factors [Formula: see text] and [Formula: see text] were calculated using the peak-frequency method, which is suitable for small-magnitude earthquakes registered in the region. Anomalously high attenuation with values of effective [Formula: see text] and [Formula: see text] ratio of less than 1 in the vicinity of the injection well was found, in comparison w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…For example, Toksoz et al (1979) and Johnston et al (1979) conclude that, for sandstone samples, Q can change from 100 to 10 based on the saturation and differential pressure. Similar results have been obtained by Hutching et al (2019) by analyzing earthquakes recorded during field operations at The Geysers geothermal field and by Wcisło et al (2017) who found high attenuation values (Q P ~ 48 and Q P /Q S < 1) analyzing seismicity induced by the injection of wastewater in the Costa Molina 2 well in southern Italy. Wandycz et al (2019) measured the variation of the anelastic attenuation based on the microseismicity recordings in Northern Poland during hydraulic stimulation of the two unconventional gas reservoirs.…”
Section: Introductionsupporting
confidence: 87%
“…For example, Toksoz et al (1979) and Johnston et al (1979) conclude that, for sandstone samples, Q can change from 100 to 10 based on the saturation and differential pressure. Similar results have been obtained by Hutching et al (2019) by analyzing earthquakes recorded during field operations at The Geysers geothermal field and by Wcisło et al (2017) who found high attenuation values (Q P ~ 48 and Q P /Q S < 1) analyzing seismicity induced by the injection of wastewater in the Costa Molina 2 well in southern Italy. Wandycz et al (2019) measured the variation of the anelastic attenuation based on the microseismicity recordings in Northern Poland during hydraulic stimulation of the two unconventional gas reservoirs.…”
Section: Introductionsupporting
confidence: 87%
“…Concerning this, our images are in partial agreement with their study: indeed, the seismic rays, travelling from the cluster of fluid-induced events to stations close to the CM2 well [ Figure 15(b)] have ray-paths partially in very high Vp/Vs materials and partially in low Vp/Vs layers. Since high Vp/Vs values retrieved by Wcisło et al (2018) mainly describe an average representation of the whole properties of the subsurface materials, we think that images retrieved by this study may partially explain their results.…”
Section: Velocity Model Interpretationmentioning
confidence: 70%
“…Also, Wcisło et al (2018), in their analyses on seismic data of injection induced cluster collected by stations very close to the CM2 injection well, retrieved high Vp/Vs values. Concerning this, our images are in partial agreement with their study: indeed, the seismic rays, travelling from the cluster of fluid-induced events to stations close to the CM2 well [ Figure 15(b)] have ray-paths partially in very high Vp/Vs materials and partially in low Vp/Vs layers.…”
Section: Velocity Model Interpretationmentioning
confidence: 94%
See 1 more Smart Citation
“…Eisner et al (2013) proposed derived theory to predict the peak frequency of observed microseismic event waveforms and showed it is consistent with surface and downhole monitoring datasets. Wcisło and Eisner (2016) developed the peak frequency methodology further and developed a new methodology to obtain more accurate results both on downhole monitoring dataset and for the surface monitoring (Wcisło et al 2017).…”
Section: Introductionmentioning
confidence: 99%